2021
DOI: 10.1093/humrep/deab133
|View full text |Cite
|
Sign up to set email alerts
|

Semen parameter thresholds and time-to-conception in subfertile couples: how high is high enough?

Abstract: STUDY QUESTION What thresholds for total sperm count, sperm concentration, progressive motility, and total progressive motile sperm count (TPMC) are associated with earlier time-to-conception in couples undergoing fertility evaluation? SUMMARY ANSWER Values well above the World Health Organization (WHO) references for total sperm count, concentration, and progressive motility, and values up to 100 million for TPMC were consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…The probability of conception depends on the quality of semen, which is reduced as one of the leading causes of male infertility ( 6 ), including reduced sperm concentration (oligospermia), decreased percentage of forward-moving sperm (weak sperm), a lower percentage of morphologically normal sperm (teratozoospermia), and complete absence of sperm in the semen (azoospermia) ( 7 ). However, basic diagnostic procedures using semen parameters are often inadequate to differentiate between fertile and infertile men ( 8 ). Among the approximately 30-40% of men with idiopathic infertility, standard semen parameters are often assessed in the ‘normal’ range ( 1 , 9 ), and even when the semen analysis is below typical average values, it is not a direct indicator or predictor of fertility outcome ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The probability of conception depends on the quality of semen, which is reduced as one of the leading causes of male infertility ( 6 ), including reduced sperm concentration (oligospermia), decreased percentage of forward-moving sperm (weak sperm), a lower percentage of morphologically normal sperm (teratozoospermia), and complete absence of sperm in the semen (azoospermia) ( 7 ). However, basic diagnostic procedures using semen parameters are often inadequate to differentiate between fertile and infertile men ( 8 ). Among the approximately 30-40% of men with idiopathic infertility, standard semen parameters are often assessed in the ‘normal’ range ( 1 , 9 ), and even when the semen analysis is below typical average values, it is not a direct indicator or predictor of fertility outcome ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, a large European study showed that a sperm concentration up to 55 million and a total sperm count of up to 145 million, which are well beyond the WHO reference levels, are associated with an earlier time to pregnancy in fertile couples [40]. Another study showed that a higher sperm count, concentration, and progressive motility beyond the WHO references are associated with better conception rates and time to conception [42].…”
Section: Discussionmentioning
confidence: 99%
“…Also in this population, a huge majority was successful within 3-4 months. In a recent study among men with semen examination results much higher than the lower 5 th percentile of results from men in couples with TTP ≤12 months (TTP timeto-pregnancy -or -conception), the time to conception was much shorter than 12 months (Keihani, Verrilli et al 2021). This altogether indicates that a population based on TTP ≤12 months is a rather mixed population.…”
Section: How To Define a Reference Population?mentioning
confidence: 92%
“…TTP ≤4 months) would encourage in-depth investigations of more men with probable male factor abnormalities. It may sound challenging but is not at all impossible (Tietze 1968, Keihani, Verrilli et al 2021).…”
Section: How To Define a Reference Population?mentioning
confidence: 99%